Relationship between asphalt mixture rut resistance from an asphalt mixture performance test and a high-temperature indirect tensile strength test - Mudiyanselage, Janaka Kumara R.A.G.R.; Auckpath Sawangsuriya; Surachet Pravinvongvuth; Kunnawee Kanitpong (Pathum Thani : Asian Institute of Technology, 2017)
The purpose of this study is to understand the Relationship between Asphalt Mixture Rut Resistance from Asphalt Mixture Performance Test and High-Temperature Indirect Tensile Strength Test. The evaluation of rut resistance using the Flow Number Test in the Asphalt Mixture Performance Test (AMPT) and the Indirect Tensile Strength Test at high Temperature (IDT) test is the main focus of this paper. And all these tests are done at standard conditions. This report contains descriptive information about the testing methods, methods of analysis, results and conclusion. Furthermore this paper includes the discussion of the recommendations and the co-relation of the above mentioned methods obtained from the final results of both tests.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Civil and Infrastructure Engineering, School of Engineering and Technology
Capstone Project (B.Sc.)-Asian Institute of Technology, 2017
Keywords: Asphalt -- Mixing; Asphalt emulsion mixtures; Asphalt -- Additives -- Testing